Positron Emission Tomography - Granov, Anatoliy; Tiutin, Leonid; Schwarz, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This handbook, written in a clear and precise style, describes the principles of positron emission tomography (PET) and provides detailed information on its application in clinical practice. The first part of the book explains the physical and biochemical basis for PET and covers such topics as instrumentation, image reconstruction, and the production and diagnostic properties of radiopharmaceuticals. The focus then turns to the use of PET in clinical practice, including its role in hybrid imaging (PET-CT). A wide range of oncological applications are discussed, including for cancers of the head and neck, breast, lung, digestive system, urinary tract, female reproductive system, and prostate, lymphoproliferative disorders, melanoma, and musculoskeletal tumors. Uses of PET in cardiology, neurology, and psychiatry are also addressed. Characteristic findings are described and illustrated by numerous images, many of them in color. This book will be of value not only for nuclear medicine physicians and radiologists but also for all oncologists, surgeons, cardiologists, neurologists, psychiatrists, and residents with an interest in molecular imaging.
Physical basis of PET -- Methodical aspects of using PET -- Diagnosis of tumors: Head and neck tumors -- Breast cancer -- Lung cancer -- Digestive tract tumors -- Stomach cancer -- Large intestine cancer -- Liver -- Pancreas cancer -- Tumors of the urinary tract and the reproductive system -- Lymphoproliferative diseases -- Cutaneous melanoma. Tumors of the locomotor apparatus -- Other oncological diseases. Tumors of the brain and nervous system.
Keywords: Nuclear medicine; Radiology; Neuroradiology; Oncology .; Nuclear Medicine; Diagnostic Radiology; Neuroradiology; Oncology